A3 Adenosine Receptor Antagonists with Nucleoside Structures and Their Anticancer Activity - Andrea Spinaci; Michela Buccioni; Diego Dal Ben; Federica Maggi; Gabriella Marucci; Beatrice Francucci; Giorgio Santoni; Catia Lambertucci; Rosaria Volpini (MDPI AG, 2022)
The overexpression of the A3 adenosine receptor (AR) in a number of cancer cell types makes it an attractive target for tumor diagnosis and therapy. Hence, in the search for new A3AR ligands, a series of novel 2,N6-disubstituted adenosines (Ados) was synthesized and tested in radioligand binding and functional assays at ARs. Derivatives bearing a 2-phenethylamino group in the N6-position were found to exert higher A3AR affinity and selectivity than the corresponding N6-(2,2-diphenylethyl) analogues. 2-Chloro-N6-phenylethylAdo (15) was found to be a potent full A3AR agonist with a Ki of 0.024 nM and an EC50 of 14 nM, in a cAMP accumulation assay. Unlike 15, the other ligands behaved as A3AR antagonists, which concentration-dependently reduced cell growth and exerted cytostatic activity on the prostate cancer cell line PC3, showing comparable and even more pronounced effects with respect to the ones elicited by the reference full agonist Cl-IB-MECA. In particular, the N6-(2,2-diphenylethyl)-2-phenylethynylAdo (12: GI50 = 14 µM, TGI = 29 µM, and LC50 = 59 µM) showed the highest activity proving to be a potential antitumor agent. The cytostatic effect of both A3AR agonist (Cl-IB-MECA) and antagonists (12 and other newly synthesized compounds) confirm previous observations according to which, in addition to the involvement of A3ARs, other cellular mechanisms are responsible for the anticancer effects of these ligands.